Integrated transcriptomics and metabolomics analysis of flower petals color transition in different phenotype of Lonicera macranthoides - Zhu, Jiayuan; Qu, Meiling; Zeng, Juan; He, Jiawei; Zhang, Jingyu; Zhou, Simin; Tong, Qiaozhen; Liu, Xiangdan; Zhou, Ribao (Frontiers in Plant Science, 2025)
BackgroundLonicera macranthoides is a classic Chinese medicinal herb with direct flower color variation among types. Our group found differences in petal color transition between Xianglei-type (XL) and Wild-type (WT). At f1-f4 stage, the two types were green, and gradually changed from green to greenish white with development, in f5-f6, WT from white to golden yellow, but XL has little color change.MethodsCombined with transcriptomics and metabolomics analysis, the color conversion differences between XL and WT petals of Lonicera macranthoides were analyzed.ResultsSignificant differential genes were identified at f1-f4, f5 and f6 in WT and XL, 14528, 7955 and 17985, respectively. At f1, the WT anthocyanin gene showed lower than XL (P < 0.05), significantly down-regulated XL and up-regulated WT at f2 (P < 0.05), but still showed higher XL than WT. XL showed significantly lower CHS (DN46824_c0_g4), CHI (DN43583_c0_g1), ANS (DN28844_c0_g1) than WT in f3. f4 stage, but again XL anthocyanins were higher than WT. We found that XL carotenoid genes all showed significantly higher levels than WT in f1 (P < 0.05). XL were significantly down-regulated at f2-f3 (P < 0.05), but not WT. Surprisingly, WT had a rapid rise in PDS (DN55130_c2_g1), ZDS (DN54194_c0_g1), and BCH (DN42921_c1_g2) at f4, far exceeding XL (P < 0.05). PSY, PDS, and ZDS genes on the carotenoid synthesis pathway, and CHS and CHI genes on the anthocyanin synthesis pathway were identified to have lower XL than WT at f5. The anthocyanin synthesis pathway CHS, CHI, and ANS were more expressed in XL than WT at f6, whereas the carotenoid synthesis pathway BCH, LCYB, and NXS were more expressed in WT than in XL. Expression validation of these genes was performed using quantitative real-time PCR (qRT-PCR). Metabolomic analysis identified a total of 158 flavonoids and one carotenoid. There were few pigment-related metabolites of f1-f4, WT had higher β-carotene content in f5 than XL, Pelargonin, marasin-3-O-galactoside had the most content in XL, and cyanidin had the most content in WT of f6. Weighted gene co-expression network analysis (WGCNA) showed that two gene modules and one gene module were strongly associated with anthocyanin and β-carotene synthesis, respectively. Genes associated with carotenoid synthesis in the modules identified by KEGG annotation were PSY, PDS, Z-ISO, ZDS, LCYB, BCH, and NXS.ConclusionOur results provide an overall understanding of the regulatory mechanisms underlying differences in petals color transition of different phenotypes of Lonicera macranthoides.